A Identifikasi Spesies Tumbuhan sebagai Sumber Belajar Botani pada Fakultas MIPA-UNM - Syamsiah; Arsal , Andi Faridah; Karim, Hilda (Biosel Biology Science and Education, 2025)
Identification, often referred to as determination, is the process of determining whether a plant is identical to a group of plants that have previously been classified and named. When a plant is to be identified, the first step is to thoroughly study the plant. All morphological traits (such as the position, shape, size, and number of parts of leaves, flowers, and fruits) need to be analyzed so that the characteristics of the plant being identified are fully understood. Botanical learning resources encompass everything used to facilitate learning about plants, including their structure, function, classification, and ecological interactions. These resources assist students or researchers in understanding various aspects of botany. This study aims to provide a comprehensive overview of the plant species present. The research method used is descriptive exploratory. The subjects of this study are the plant species found at the Faculty of Mathematics and Natural Sciences (MIPA) at UNM. Data collection was conducted in two stages: exploration and field observation. The results of this method were then analyzed by listing all identified plant characteristics in tables and photographs, which were then described descriptively. The findings indicate that there are 44 plant species at the Faculty of MIPA-UNM, belonging to the families Arecaceae, Combretaceae, Agavaceae, Euphorbiaceae, Myrtaceae, Iridaceae, Solanaceae, Araliaceae, Liliaceae, Meliaceae, Sapotaceae, Apocynaceae, Malvaceae, Anacardiaceae, Moraceae, Heliconiaceae, Amaranthaceae, Rubiaceae, Cannaceae, Verbenaceae, Rutaceae, Annonaceae, Nytainaceae, Vitaceae, and Crassulaceae. Therefore, the plant species found at the Faculty of MIPA-UNM are well-suited to serve as botanical learning resources.  Keywords: Identification, Plants, Faculty of MIPA-UNM